Development of Digital LKPD Based on Problem-Based Learning on the Topic of the Human Digestive System - Hani Irawati; Senja Amalia Rahmawati (Green Publisher Indonesia, 2024)
The biology learning process in some schools so far still uses teaching materials in the form of printed student worksheets (LKPD). The printed LKPD used still has several shortcomings, including not yet attractive, the images are still black and white and inflexible, so it is necessary to develop LKPD that suits the needs of students in biology learning materials. The purpose of this research is to develop digital LKPD based on Problem Based Learning digestive system material in humans. The type of research carried out is R&D with the ADDIE model which consists of 5 stages, namely: Analysis, Design, Development, Implementation, dan Evaluation. Data collection techniques with questionnaires while the data collection instruments used are in the form of questionnaires of assessment sheets of material experts, media experts, education experts, biology teachers and student responses. Product trials are carried out to learners divided into small group tests and large group tests. The results of this study show that: Problem-Based Learning digital LKPD based on digestive system material in humans which is assessed by material experts, media experts, education experts, and biology teachers in the